Human Trafficking for Sexual Exploitation - Stevanović, Zoran (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
Human trafficking for sexual exploitation is a worldwide problem that is present in all communities. It is particularly pronounced in countries that are in political and economic transition, undeveloped and developing countries, countries in war and post-conflict regions. The victims were mainly people from the margins, from vulnerable social groups and poor communities, which makes them suitable for manipulation and consequently to be exploited. A victim of human trafficking can become anyone regardless of gender, race, age and education, mostly due to forced labour, begging and organ trafficking. The issue of human trafficking is a multidisciplinary issue, and it must involve everyone- from police, medical and social workers to the ordinary citizens who may also have a large stake in combating the phenomenon of slavery of the 21st century. The problem of human trafficking for prostitution particularly affects women and children as a result of the new social and political reality caused by the restrictive immigration policies of Western European countries and the militarization of certain regions.